Actuality of Aristotle - Machura, Piotr (Folia Philosophica, 2018)
Review of Enrico Berti's book Arystoteles w XX wieku, trans. into Polish by A. Dudzińska-Facca, D. Facca, Wydawnictwo Instytutu Filozofii i Socjologii PAN, Warszawa 2015